Sociolinguistica : Internationales Jahrbuch für europäische Soziolinguistik / International Yearbook of European Sociolinguistics / Annuaire International de la Sociolinguistique Européenne (De Gruyter, 1987)
This yearbook deals with language problems in Europe, especially with the conditions and consequences of Europe's economic and political integration. Each volume is dedicated to a particular topic, but also contains book reviews, reports on the sociolinguistic research in individual countries, and a comprehensive bibliography on new sociolinguistic publications in Europe.